The Political Economy of Sharia Regional Regulation on Halal Tourism Policy in Lombok, Indonesia - M. Syamsurrijal M. Syamsurrijal; Achmad Nurmandi; Hasse Jubba; Mega Hidayati (Khazanah Sosial, 2021)
This study analyzes the political economy in implementing halal tourism policies in Lombok, West Nusa Tenggara. The concept of political economy is used to find and analyze the implementation of halal tourism policies on social, economic and political life in Lombok, West Nusa Tenggara. The data in this study were collected through interviews, documentation and literature review. The data source comes from primary data collected using interviews conducted with policymakers about halal tourism. In comparison, the secondary sources in this study came from the Central Statistics Agency, journals, and seeds that are considered relevant to this research. Data analysis was carried out in three stages, first, data reduction; second, data verification and third, withdrawal. The results of this study found three important things in the implementation of halal tourism. First, halal tourism is the government's strategy to introduce Lombok to the international world. Second, Halal tourism is the government's strategy to grow the community's economic sector. Third, Halal tourism is the government's political economy strategy to strengthen the legitimacy of political power among the community and strengthen the relationship between local governments and the central government as a form of loyalty from regional heads to the central government.